Technology of Forming Future Teachers’ Readiness for Pedagogical Improvisation - Bashkir, Olha; Panchenko, Violetta; Osova, Olha; Zhytnytska, Anastasiia (Educational Challenges, 2021)
The article grounds the relevance of the special preparation of students of pedagogical universities for pedagogical improvisation based on the analysis of psychological and pedagogical literature and the ways in which future teachers acquire professional knowledge and skills. Having analyzed the content of the educational programs of psychology and pedagogy we proved that no purposeful training of future teachers for pedagogical improvisation has been organized. It caused the need for developing an appropriate technique. The purpose of the article is to develop a technique to form future teachers’ readiness for pedagogical improvisation in the process of studying psychological and pedagogical disciplines. Methodology. The research was conducted with the application of theoretical (analysis of psychological and pedagogical literature to define a conceptual-categorical apparatus; grounding the technique of forming future teachers’ readiness for pedagogical improvisation) and empirical methods (surveys, questionnaires, testing, observation, conversation, dialogue, methods of expert evaluation, self-assessment analysis of learning outcomes, content of educational programs of psychological and pedagogical disciplines). In the course of the research the following results were achieved: the essence of the concepts «readiness for pedagogical improvisation», «learning technique» was defined; structural components of readiness for pedagogical improvisation were singled out; surveys, interviews and questionnaires were conducted among the future teachers to identify their level of readiness for pedagogical improvisation. Moreover, the research contributed to the development of a technique to form future teachers’ readiness for pedagogical improvisation, which led to the gradual formation of students’ skills to improvise. The conducted research allowed us to draw the conclusion that the readiness for pedagogical improvisation is a stable individual quality that integrates the values, knowledge, skills, which should be formed in several stages. Motivational-targeted stage was aimed at stimulating the development of positive motivation for improvisation; content and procedural stage that provided for acquiring the necessary knowledge and skills of pedagogical improvisation; evaluation-reflexive stage involving evaluation and correction of personal and professional development, content, forms and methods of training.